1999
DOI: 10.1103/physrevlett.83.5346
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Doping of Amorphous Carbon Surfaces

Abstract: The surface properties of amorphous carbon (a-C) are studied using first-principles electronic structure methods. The effect of nitrogen doping near the surface and, in particular, the effect of nitrogen on the work function is studied by doing a series of nitrogen substitutions near the surface. It is found that the work function is reduced by nitrogen doping of the a-C surface at "on top of the surface" sp 1 and sp 2 sites. Nitrogen doping by low energy ion bombardment is suggested as a doping method to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…[16] The resulting carbon was amorphous, as revealed by the XRD patterns (Figure 5a), and contained 4.0 at% N, as determined by EA. [16,30,31] The fabricated N-doped carbon was amorphous with a flaky morphology, as shown by the SEM and TEM images (Figure 5d-f). [30] The XPS profile of N revealed the presence of graphitic N (0.92 at%) at 401.4 eV, pyrrolic N (1.84 at%) at 400.1 eV, and pyridinic N (1.44 at%) at 398.4 eV.…”
Section: Effects Of N-doped Carbon Electrocatalyst Layermentioning
confidence: 86%
“…[16] The resulting carbon was amorphous, as revealed by the XRD patterns (Figure 5a), and contained 4.0 at% N, as determined by EA. [16,30,31] The fabricated N-doped carbon was amorphous with a flaky morphology, as shown by the SEM and TEM images (Figure 5d-f). [30] The XPS profile of N revealed the presence of graphitic N (0.92 at%) at 401.4 eV, pyrrolic N (1.84 at%) at 400.1 eV, and pyridinic N (1.44 at%) at 398.4 eV.…”
Section: Effects Of N-doped Carbon Electrocatalyst Layermentioning
confidence: 86%
“…Kaukonen et al19 suggested based on their density functional theoretical (DFT) calculation that a single N atom substitution at a sp 3 or sp 2 site in an a‐C subsurface layers increases the total density of states (TDOS) below the energy gap resulting in Fermi energy ( E f ) level moving down and the work function increasing. Whereas substitution on the sp 1 and sp 2 rings in the outer surface leads to TDOS increase near the conduction band edge with the Fermi level moving up and the work function decreasing.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this interpretation it seems that N substitution in this study is dominant at the sp 1 , sp 2 rings in the outer surface for ''SN'' type N-doped films, that is, the ''SN'' atomic species substitute preferentially at the sp 1 and sp 2 rings compared to the ionic N species. Nitrogen doping of a-C is known to increase the sp 2 /sp 3 ratio and density functional theoretical (DFT) calculations 19 suggests that N atoms positioned at an sp 3 site decreases their coordination number with resulting sp 2 N (or N with a non-planar threefold coordination). It therefore seems logical that N atoms positioned at an sp 1 or sp 2 sites could increase the co-ordination number with resulting sp 2 N or sp 3 N respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Capacitance Kelvin and the I-V probes suggest that in the N-doped DLC (without the use of sweep plate) the CPD and the density of state (DOS) decreased, indicating a Fermi level rise. 11 However, Kaukonen et al 13 suggested based on their density function theoretical (DFT) calculation that a single N atom substitution at an sp 3 or sp 2 site in an a-C subsurface layers increases the total density of states (TDOS) below the energy gap, resulting in Fermi energy (E f ) level moving down and the increase in work function. However, substitution on the sp 1 and sp 2 rings in the outer surface leads to TDOS increase near the conduction band edge with the Fermi level moving up and the work function decreasing.…”
Section: Endothelial Cellular Interactionmentioning
confidence: 98%
“…3 ratio and density function theoretical (DFT) calculations 13 suggests that N atoms positioned at a sp 3 site decreases their coordination number with resulting sp 2 N (or N with a nonplanar threefold coordination). Nitrogen incorporation into DLC normally reduces the contact angle (increases the surface energy), 1 though it seems that N-neutral specie ("SN") doping increased the contact angle in this study (Figure 1).…”
Section: /Spmentioning
confidence: 99%